Accumulation and toxicological risk assessment of Cd, As, Pb, Hg, and Cu from topsoils of school playgrounds at Obio-Akpor LGA Rivers State Nigeria - Chioma, Okereke; Emmanuel, Agomuo; Peter, Amadi (International Journal of Scientific World, 2017)
The adverse health effects associated with heavy metal pollution have become a subject of topical discussion. Using standard methods, this study evaluated the accumulation and toxicological risks of heavy metal deposition on top soils of school playgrounds in Obio-Akpor LGA. Results obtained from the top soils, sampled from 10 different schools showed that the concentration of heavy metals assessed, followed the trend; Hg<As<Cd<Pb<Cu. Marginal differences between the test and control samples were observed for the geoaccumulation index of the heavy metals except for copper. For the contamination factor, FCUA had the least results for cadmium (0.31) but highest in arsenic (0.016) while OPS, UDPS and RBPS recorded the highest contamination factor for lead, mercury, and copper respectively. The results for the pollution load index and degree of contamination of the test sites showed that the sites were unpolluted and had low contamination status, while the enrichment factors showed the deposition of only cadmium to be of a natural origin, and the rest of the heavy metals resulted from anthropogenic sources. The trend from the hazard quotient was Pb>Hg>Cu>Cd>As while the highest (0.0213) and least (0.0162) total hazard index value occurred at RBPS and MOM respectively. These values obtained for this study indicate that the school playground's soils are still within the recommended heavy metal content safe levels.